Enxertos de mucosa queratinizada, uma abordagem com materiais xenógenos: revisão de literatura - Cruz, Juliano Passos da (2022)
Introduction: The keratinized gingiva is one of the types of mucous membranes present in the oral cavity, having in its differential, keratinized cells, endowed with connective filaments adhered to the tooth and to the alveolar bone, thus forming a kind of physical protection against bacterial invasion, physical or trauma. infections. In certain cases where there is loss of this tissue, it is necessary to perform the use of grafting techniques, using autogenous materials, considered the gold standard. However, in the absence of this type of graft, the use of xenogenous biomaterials is an effective substitute when there are limitations in the use of autogenous materials. Objective: To verify the possibility of using xenogenous materials as a substitute for autogenous material, in the use of biomaterial to gain keratinized mucosa, through a literature review. Methodology: A bibliographic review was carried out using keywords: Mucograft®, Gum Graft and Keratinized Gingiva, in the PUBMED, Scielo and Google Scholar databases. Selected national and international scientific articles, book chapters and dissertations. Studies that were not relevant to the topic were excluded, and at the end, 33 articles, on the use of xenogeneic grafts to gain keratinized mucosa. Results: The use of xenogenous biomaterials as substitutes for autogenous grafts has promising results, showing ideal values in obtaining keratinized mucosa, providing better aesthetics, less pain, shorter surgical time and lower cost compared to autogenous material. Conclusion: Finally, the use of biomaterials is a great proposal in the replacement of autogenous graft, when there are limitations in its use, in addition to unlimited availability, xenogeneic biomaterials allow the gain of keratinized mucosa in satisfactory amounts, having the Mucograft® by Geitilsh one of the most promising products, due to its differentiated structure.